Using data to promote inclusion through early childhood mental health consultation - Clayback, Kelsey A.; Partee, Ann M.; Williford, Amanda P.; Downer, Jason T.; Parker, Kyra; Lhospital, Ann S. (Frontiers in Education, 2025)
IntroductionEarly childhood educators continue to need support to build their capacity to promote positive social and emotional development and address challenging behavior when it occurs, without resorting to exclusion. One approach to improve the experiences and outcomes of young children through better support to educators is Early Childhood Mental Health Consultation (ECMHC). ECMHC is an evidence-based intervention that pairs a mental health professional (i.e., “consultant”) with early childhood educators to build the capacity of providers to promote inclusion by supporting young children's social and emotional development.MethodsIn this paper, we describe a model of ECMHC that combines data-driven action planning and an individualized approach to build educators' capacity to implement social and emotional teaching practices with fidelity. The model begins with in-context classroom observations of child engagement and teaching practices, as well as a teacher-report of child behavior. Based on this observational baseline data, a standardized formula selects a personalized set of social and emotional teaching strategies recommended for the focus of consultation, based on the strengths and challenges of the teacher and child. Strategies included foundational strategies (e.g., fostering strong teacher-child relationships), flexible strategies (e.g., using cues and visuals), and targeted strategies (e.g., supporting problem-solving skills). Consultants and teachers then collaboratively work together to select strategies to focus on in consultation, allowing for flexibility and individualization based on individual teacher and child strengths and challenges.ResultsWe address the following two aims: (1) examine teaching practices and children's behavior at the beginning of consultation and how these data resulted in different recommended teaching strategies, based on our standardized formula, (2) present three case examples to further illustrate how these data guided consultation to improve social and emotional teaching practices during the 2023 to 2024 school year. We found that this baseline data collection and the subsequent data-driven process for selecting strategies was feasible in that all consultants and teachers served by ECMHC were able to use it. We also found variability in baseline data and the associated ECMHC teaching strategies recommended, suggesting that the measures were sensitive to unique classroom needs and individualized recommended strategies accordingly.DiscussionWe discuss how this approach allowed consultants to tailor ECMHC services to the unique strengths and challenges of each child and teacher dyad, while being firmly grounded in empirical research and previously validated assessments.